High output power erbium-ytterbium doped cladding pumped fiber amplifier - Harun, Sulaiman Wadi; Moghaddam, M.R.A.; Ahmad, Harith (John Wiley & Sons, 2010)
The performance of a high output power Erbium-Ytterbium doped fiber amplifier (EYDFA) pumped by a 927 nm laser diode are proposed and experimentally investigated. The EYDFA provides a flat gain and output power higher than 23 dBm in the wavelength region from 1545 to 1566 nm using a double-pass configuration. A broadband fiber Bragg grating is used in the double-pass EYDFA to allow a double-propagation of the test signal in the gain medium and thus improves the gain and output power characteristics of the amplifier. The maximum output power of 390 mW is obtained at the maximum 927 nm pump power of 4.1 W which translates to a power conversion efficiency of about 10%.